Reasons of the non Use of the masculine condom among patient with onfection or not for HIV - Galvão, Marli T.G.; Ramos-Cerqueira, Ana Teresa A.; Ferreira, Maria de Lourdes S.M.; Souza, Lenice R. (Brazilian Journal of Sexually Transmitted Diseases, 2002)
From the emergence of the aids the use of the masculine condom in the sexual relationships is one way to impede the spread of the disease. This research had for objective to obtain and to analyze verbal reports of reasons attributed for the non use of the condom in the sexual relationships among bearers or not of HIV. Fourteen patients were interviewed with age between 23 and 30 years. 78% had equivalent education to the first incomplete degree. 50% referred lime of conviviality with the companion (the) of a larger period or equal to six years. The heterosexual way was the main infection form and 58% presented aids. Two men were HIV negative, being there companions HIV positive and they didn’t make use of masculine condom. The reasons attributed by the men for the non use were: indisposition caused by the use, interference in the manliness, not to be own for “males", decrease of the pleasure, ignorance of the new infection and discredit as for the risk of contaminating. The women attributed the non-use to the companions’ resistance in doing it. what takes them to accept that imposition for fear of lose them. A woman referred to ignore the reinfecção possibility for HIV. and one of the women referred not to like of the condom. Men and women, except for a couple, told to have knowledge of the complications for the non-use. Those data point the need to intensify a work not just informative, but that seeks attitude changes regarding to sexual e role, the vision of the sex in a special way w ith sick patients or bearers of HIV of both sexes, as well as of perfecting the possibility of the protection independently of the partner.